Analisis User Experience terhadap Penggunaan Aplikasi Smart Tourism dengan Pendekatan Design Thinking - Dian Megah Sari; Adi Heri; Nurdiana Rasjid (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The rise of internet and smartphone users who have directly changed people's lifestyles has become one of the strategies for optimizing the tourism industry through the use of technology towards digital to be better known by the wider community, in this case a smart tourism application was built to make it easier for tourists to access information covering all tourism sectors in the province of West Sulawesi. User experience (UX) is an important and important factor for an application in providing convenience and a good experience to users of the accessibility of a product being offered. User experience analysis in this study uses the design thinking method so that later it will produce a very good level of user experience (UX). The evaluation results obtained later from the use of the smart tourism application will be tested using the System Usability Scale (SUS) and User Experience Questionnaire (UEQ) calculations which include learning ability, usability, and group impressions of attractiveness, sharpness, efficiency, dependence, stimulation, novelty where the results of the overall test get very good results (good and excellent)